"Informalisation of employment and career trajectories in the gig economy: evidence from ehailing drivers Cape Town" - Zimuto, Samson (Department of Information Systems, 2025)
Problem Statement: The rate of technological development, ehailing adoption, work fairness, and industry performance within the gig-economy are well-studied globally. However, the South African context remains underexplored. Research on career trajectories and informality in this sector has been limited by insufficient data and the absence of robust frameworks. Research Objective: The main aim of this research is to investigate the impact of the gig economy on informalisation of employment and individual career trajectories of gig workers, by assessing the degree of formality in ehailing, the career expectations and planning of ehailing drivers. To this end, a post-positivist research philosophy was adopted. Research Design: The study collected data using semi-structured interviews. The sample for the study was constituted of 30 ehailing drivers from Cape Town. The study employed an exploratory approach which enables the researcher to probe for more information based on initial responses from the participants and a thematic approach for data analysis. The study adopted the Spectrum of Informality (SOI) and the Social Cognitive Career Theory (SCCT) frameworks to guide the research. The SCCT framework was customized to focus on ehailing-specific and related factors termed job specific determinants of career choices. Findings: The study findings depict the ehailing driver's job as a more informal to semi-formal role on SOI. Wage determination, compliance and legal benefits mapped as Informal on the SOI. While contracts, income stability, hours of work and supervision plotted as Semi-Formal on the SOI. The study found that most drivers initially planned to continue in their historical careers and expected consistent growth over time, while some maintained ehailing as a part-time role. The study found that joining ehailing significantly changed most drivers' career progression, with others considering it a complete career change. However, when investigating satisfaction, this study found that drivers are not satisfied with the support received from ehailing companies, their current incomes and other factors. Research Contribution: The study was situated at the intersection of labour economics and information systems research around the gig economy. This study contributes to literature on ehailing studies and career trajectories of gig workers. In addition, the aspect of informality and the mapping of the ehailing driver's role is a key contribution that could aid policy making. The updating of the SCCT model and its application to ehailing careers also created a good opportunity for further research in this area.